2019
DOI: 10.1016/j.foodcont.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

A study of food safety knowledge, practice and training among food handlers in Ireland

Abstract: Food safety knowledge, practice and training were examined among 689 food workers in Ireland. Parameters such as role, years worked, level of food safety training acquired, and establishment were all found to have a significant effect (p-values <0.01) on knowledge score. It is notable that 28% of all respondents claimed 'never' to have received food safety training, suggesting insufficient compliance with this legislative requirement. Notably, absence of training only accounted for 1% (n=1) of all canteen work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 36 publications
2
32
0
1
Order By: Relevance
“…We found that, in general, restaurant kitchen chefs have higher KSs regarding "Hands should be washed with soap and water or by using hand sanitizer before preparing food" and "Hands should be washed with soap and water or by using hand sanitizer after using the toilet". Similar findings have been reported for restaurant workers in Jordan [21], food workers in Ireland [36], food handlers in food service establishments in the United Arab Emirates [24], and food handlers in restaurants in Kuwait [17]. We also found that the KS for Chinese restaurant kitchen chefs regarding "Hands should be washed with soap and water or by using hand sanitizer after touching used cutlery" (74.8%) was significantly lower.…”
Section: Discussionsupporting
confidence: 86%
“…We found that, in general, restaurant kitchen chefs have higher KSs regarding "Hands should be washed with soap and water or by using hand sanitizer before preparing food" and "Hands should be washed with soap and water or by using hand sanitizer after using the toilet". Similar findings have been reported for restaurant workers in Jordan [21], food workers in Ireland [36], food handlers in food service establishments in the United Arab Emirates [24], and food handlers in restaurants in Kuwait [17]. We also found that the KS for Chinese restaurant kitchen chefs regarding "Hands should be washed with soap and water or by using hand sanitizer after touching used cutlery" (74.8%) was significantly lower.…”
Section: Discussionsupporting
confidence: 86%
“…(2012) , age and experience did not seem to have significant effects on the findings. There are also some studies that have found no significant association of gender and marital status with food safety knowledge of food handlers ( Taha et al., 2020 ; Alqurashi et al., 2019 ; Carbas et al., 2013 ; Gruenfeldova et al., 2019 ; Kunadu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the trained participants were superior in knowledge, attitude, and self-reported practices to the untrained participants. Training has been proved effective in improving food safety and hygiene knowledge in many studies ( McIntyre et al., 2013 ; Gruenfeldova et al., 2019 ; da Cunha et al., 2014 ; Soon et al., 2012 ; Taha et al., 2020 ). However, compared to knowledge and attitude, self-reported practices of trained food handlers seemed a bit weak in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, only a few hospital food handlers correctly indicated thawing in the refrigerator as the best way to safely thaw frozen meat as well as 7 days as the correct maximum duration for which prepared ready-to-eat TCS food prepared in-house could be stored at 5˚C. This can be attributed to the fact that most of the hospital food handlers have not received training on cold storage durations [43][44]. Training programs geared toward food storage temperatures and duration can improve the food safety practice of food handlers [45].…”
Section: Knowledge On Food Handling Temperaturesmentioning
confidence: 99%